Association between polymorphisms of IL33 and IL37 and atopic dermatitis - O. A. Svitich; O. Yu. Olisova; M. B. Potapova; E. A. Meremianina; N. D. Rasskazova; E. A. Belokopytova; A. A. Solodkova; A. A. Murzina; I. B. Semenova; A. G. Upatova (Медицинская иммунология, 2024)
Atopic dermatitis (AD) is a chronic recurrent inflammatory disease accompanied by severe itching. One of the leading mechanisms underlying the development of AD is an imbalance of the Th1/Th2 cells immune response, which leads to an increased production of inflammatory mediators, including IL-1 family. The IL-1 family includes the recently discovered IL-33 and IL-37, and their role in the pathogenesis of AD has been actively studied. IL-33 functions as an alarmin that can induce IL-31 production, thereby leading to skin barrier impairment, pruritus and scratching. Having both immunomodulatory and immunosuppressive properties, IL-37 suppresses leukocyte infiltration of the affected skin and reduces the activity of proinflammatory cytokines. The aim of our study was to search for associations between gene polymorphisms of IL33, IL37 genes, and risk of AD. A total of 98 patients with moderate and severe AD were included in the study. The control group included 72 healthy volunteers. Polymorphic markers were determined in peripheral blood. After extraction of total RNA, polymorphic markers rs7019575 in the IL33 gene, rs3811046 and rs3811047 in the IL37 gene were analyzed using RT-PCR. There was no statistically significant difference in allele frequency and genotype distribution of rs7019575 (IL33) and rs3811047 (IL37). Studying the rs3811046 polymorphic marker in the IL37 gene showed that the risk of AD was almost 2 times lower for the G allele carriers and more than 2-fold higher for TT homozygous carriers. The haplotype analysis revealed that the GTAA and TTGG haplotypes of IL37 were associated with AD, thus increasing the risk of AD development by 2 and 10 times, respectively. In conclusion, SNP markers identified in this study can be used to predict the risk of AD development in the subjects with a positive family history of atopic diseases.